2015
DOI: 10.1071/wr14222
|View full text |Cite
|
Sign up to set email alerts
|

How many are there? Multiple-covariate distance sampling for monitoring pampas deer in Corrientes, Argentina

Abstract: Context The pampas deer (Ozotoceros bezoarticus) is an endangered species in Argentina. Scarce information exists about one of the four last populations that survive in Corrientes province, where direct counts estimated a population of <500 individuals. Aims To evaluate the status of the pampas deer population in Corrientes by applying a standardised methodology and to develop methodological recommendations for future deer monitoring. Methods We conducted six population censuses between 2007 and 2010, using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…In this regard, [13] stated that six globally threatened bird species, distributed within the Aguapey basin, were highly impacted by the presence of tree plantations, which not only affected their breeding habitats but also impeded their ability to disperse between habitat patches. The impacts of temperate grassland fragmentation have also been reported in regard to the endangered Pampas deer [31]; however, a recent study suggested that Pampas deer could be positively selecting grassland patches within young tree plantations as refuge against predators [61]. The ecological effects are therefore complex and warrant further study.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, [13] stated that six globally threatened bird species, distributed within the Aguapey basin, were highly impacted by the presence of tree plantations, which not only affected their breeding habitats but also impeded their ability to disperse between habitat patches. The impacts of temperate grassland fragmentation have also been reported in regard to the endangered Pampas deer [31]; however, a recent study suggested that Pampas deer could be positively selecting grassland patches within young tree plantations as refuge against predators [61]. The ecological effects are therefore complex and warrant further study.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas habitat‐based population models used presence‐only locations in a spatially explicit manner to develop deer population estimates, distance sampling models incorporated the distance and direction from observers to each deer to model the detection function and estimate density. We used the multiple covariate distance sampling (MCDS) engine (Marques and Buckland ) to estimate the detection function for deer in response to the proportion of forest cover and terrain ruggedness measured at 2 scales in a GIS (90 m and 120 m) and deer density (Anderson et al , Zamboni et al ). We further extrapolated deer abundance statewide based on the area surveyed during spotlight surveys.…”
Section: Methodsmentioning
confidence: 99%